2021
DOI: 10.1097/meg.0000000000002287
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of sofosbuvir/ledipasvir and sofosbuvir/daclatasvir in the treatment of hepatitis C in patients with decompensated cirrhosis

Abstract: Background Hepatitis C virus (HCV)-related decompensated cirrhosis is a severe life-threatening illness. The safety of direct-acting antivirals (DAAs) has opened a gate of hope for that subgroup of patients who were previously contraindicated for interferon therapy. Objective We aimed at the investigation of the safety and efficacy of different DAAs regimens in the treatment of HCV-related decompensated cirrhosis patients, to determine sustained virological response (SVR)12 rates and to analyze the factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In this study increasing age does not depict any significant association between the achievement of SVR and ETR similar to the study done in the past but there was a significant association observed between decreasing age and attainment of SVR in a study done by Ahmed et al [24] and Mushtaq et al [18]. Another study done by El Kassas et al showed age >50 years have a significant association with SVR [22].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In this study increasing age does not depict any significant association between the achievement of SVR and ETR similar to the study done in the past but there was a significant association observed between decreasing age and attainment of SVR in a study done by Ahmed et al [24] and Mushtaq et al [18]. Another study done by El Kassas et al showed age >50 years have a significant association with SVR [22].…”
Section: Discussionsupporting
confidence: 79%
“…In this study, ALT remained the same for patients who attained ETR and SVR but an increase in ALT levels was observed who did not achieve ETR and SVR from 45.33±2.89 to 61.00±0 but the association was insignificant, but a study done by El Raziky et al and El Kassas showed a decrease in ALT levels with significant association [22,23].…”
Section: Discussionmentioning
confidence: 41%
“…There was no improvement in efficacy outcomes for any experimental arm versus SOC. Adverse events reported for the investigational regimens were broadly consistent with their known safety profiles, 11 , 12 , 28 , 29 , 30 , 31 , 32 and all treatments were well tolerated.…”
Section: Discussionmentioning
confidence: 55%
“…Genetic testing of patients using the indicated antiviral agents may be useful to ensure optimal therapeutic efficacy. Alternatively, the new hepatitis C therapies such as sofosbuvir, ledipasvir, and daclatasvir, which are not known to be affected by the mutations in IFNL3 and IFNL4 genes, can be used ( 64 ). However, it has been reported that selected polymorphisms in the ABCB1 and HNF-α genes influence the concentration of sofosbuvir plasma metabolite ( 65 ).…”
Section: Discussionmentioning
confidence: 99%